Implanted Biofuel Cell Operating in a Living Snail - Halámková, Lenka; Halámek, Jan; Bocharova, Vera; Szczupak, Alon; Alfonta, Lital; Katz, Evgeny (Journal of the American Chemical Society, 2012)
Implantable biofuel cells have been suggested as sustainable micropower sources operating in living organisms, but such bioelectronic systems are still exotic and very challenging to design. Very few examples of abiotic and enzyme-based biofuel cells operating in animals in vivo have been reported. Implantation of biocatalytic electrodes and extraction of electrical power from small living creatures is even more difficult and has not been achieved to date. Here we report on the first implanted biofuel cell continuously operating in a snail and producing electrical power over a long period of time using physiologically produced glucose as a fuel. The “electrified” snail, being a biotechnological living “device”, was able to regenerate glucose consumed by biocatalytic electrodes, upon appropriate feeding and relaxing, and then produce a new “portion” of electrical energy. The snail with the implanted biofuel cell will be able to operate in a natural environment, producing sustainable electrical micropower for activating various bioelectronic devices.